2017
DOI: 10.1186/s12913-017-2395-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of emergency nurse practitioner service in the management of patients presenting to rural hospitals with chest pain: a multisite prospective longitudinal nested cohort study

Abstract: BackgroundHealth reforms in service improvement have included the use of nurse practitioners. In rural emergency departments, nurse practitioners work to the full scope of their expanded role across all patient acuities including those presenting with undifferentiated chest pain. Currently, there is a paucity of evidence regarding the effectiveness of emergency nurse practitioner service in rural emergency departments. Inquiry into the safety and quality of the service, particularly regarding the management of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 74 publications
1
31
0
1
Order By: Relevance
“…at the point of the search. The previously unpublished manuscript was subsequently published in 2017 [ 42 ]. All included studies were conducted between 2006 and 2016.…”
Section: Resultsmentioning
confidence: 99%
“…at the point of the search. The previously unpublished manuscript was subsequently published in 2017 [ 42 ]. All included studies were conducted between 2006 and 2016.…”
Section: Resultsmentioning
confidence: 99%
“…APN involves: “nurses working in advanced roles have additional training and work beyond RNs' scope of practice?” (Maier & Aiken, ). In previous research, researchers have found advanced practice nursing to be as good as or, in some cases, even better than physician‐led care (Cooper, Lindsay, Kinn, & Swann, ; Roche, Gardner, & Jack, ; Wilson, Zwart, Everett, & Kernick, ). Nurse‐led care has been shown to have a positive impact on wait times (Hiza, Gottschalk, Umpierrez, Bush, & Reisman, ; Jennings, Clifford, Fox, O'Connell, & Gardner, ), patient satisfaction (Cooper et al, ; Jennings et al, ; Martinez‐Gonzalez et al, ), and quality of care (Jennings et al, ; Martinez‐Gonzalez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…(Maier & Aiken, 2016). In previous research, researchers have found advanced practice nursing to be as good as or, in some cases, even better than physician-led care (Cooper, Lindsay, Kinn, & Swann, 2002;Roche, Gardner, & Jack, 2017;Wilson, Zwart, Everett, & Kernick, 2009).…”
mentioning
confidence: 99%
“…In a small emergency department in Australia, 61 patients were examined by physicians with the help of emergency nurses, and the waiting time and length of stay were calculated as 13.2 min and 116 min, respectively. Nevertheless, no evidence is provided in terms of comparisons with other situations related to these parameters in the research [19].The purpose of this study is to ensure that nurses recommended for ESs in Turkey are employed as advanced nurses (ANs) after receiving 2+ years of training, after they complete a normal nursing education. ANs must have the authority to write prescriptions for routine diseases (colds, headaches, Processes 2019, 7, 48 3 of 18…”
mentioning
confidence: 99%
“…In a small emergency department in Australia, 61 patients were examined by physicians with the help of emergency nurses, and the waiting time and length of stay were calculated as 13.2 min and 116 min, respectively. Nevertheless, no evidence is provided in terms of comparisons with other situations related to these parameters in the research [19].…”
mentioning
confidence: 99%